Comparative Analysis of Selective Bacterial Colonization by Polyethylene and Polyethylene Terephthalate Microplastics - Song, Yuhao; Zhang, Baoxin; Zou, Lianwei; Xu, Feng; Wang, Yaqi; Xin, Shaoqi; Wang, Yang; Zhang, Hongyuan; Ding, Ning; Wang, Renjun (Frontiers in Microbiology, 2022)
In this study, we report the biodiversity and functional characteristics of microplastic-attached biofilms originating from two freshwater bacterial communities. Even though the microplastic-biofilm (MPB) diversities are mostly determined by original bacteria instead of microplastic types, the results from 16S rRNA amplicon sequencing still showed that the dynamic biofilm successions on different microplastics were highly dissimilar. Furthermore, the analysis of biomarkers indicated distinct bacterial species with significant dissimilarities between different MPBs, which further determined the associated functions. The co-occurrence networks showed distinct interconnective characteristics in different MPBs: The structure of MPB incubated in the lake water sample was more robust under environmental stresses, and bacteria in the tap water MPB interacted more cooperatively. Regarding this cooperative interaction, the analysis of functional prediction, in this study, also showed that more symbionts and parasites colonized on microplastics in the tap water than in the lake water. Moreover, it was suggested that MPBs were more easily formed in the tap water sample. The overall results revealed significant dissimilarities in bacterial diversity, succession, and associated functions between MPBs, in which bacterial species with specific functions should be taken seriously.